(untitled) (International Journal of Banking and Finance, 2013)
Financial intermediation is a value-enhancing service. Banks are among the most important financial institutions in a modern economy for that service. Conventional banks use rates of interest (charged to clients and paid to depositors) on both the assets and the liabilities sides. Since interest is prohibited in Islam, Islamic financial experts have developed a number of financial instruments that avoid any involvement in interest. They take the form of either risk-and-reward sharing or trading in commodities/assets to price assets. In this paper we describe the basic features of the most important among these financial instruments. Even though Islamic banks emerged in response to market needs of Muslim clients, they are not religious institutions. Like other banks, these are profit seeking institutions, simply following a different model of financial intermediation. While it is the preferred way of banking for one fifth of humanity, it offers a wider choice of financial products to all by generating a number of benefits for the society. The successful operation of Islamic financial institutions has proven that this new model of financial intermediation is not only viable, but in many aspects, it is rather superior to the conventional model. The appealing features of the Islamic model have attracted world-wide attention. Islamic financial industry which started as a niche market in early 1970s in the Middle East has made a place for it in more than fifty countries around the globe and has grown into a multi-trillion dollars industry. This paper attempts to explain the basic features of this fascinating model.